ANTESEDEN KEPUASAN KONSUMEN PADA SUPERMARKET BAHAN BANGUNAN MITRA 10, SIDOARJO - Eva Desembrianita; Noneng R Sukatmadiredja (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2018)
This research was conducted to analyzed the effect of independent variables consisting of serviceinnovation, customer service and customer relationship management on the variables of customersatisfaction. This research is a survey research by distributing questionnaires with a nonprobabilitysampling design, to 96 respondents / consumers of Mitra 10, Sidoarjo. Data analysistechnique uses multiple linear regression. The results showed that Fcount of 72.595 was greaterthan Ftable (72.595> 2.699). The t test on each variable gives the results of service innovation hasa significant effect on consumer satisfaction because t table is 1,984, the value of t count in X1 is5.614 (t count> t table). Customer service has a significant effect on consumer satisfaction becausethe tcount value at X2 is 2.834 (t count> t table). Customer Relationship Management (CRM) has asignificant effect on consumer satisfaction because thitung in X3 is 3.817 (thitung> t table). ServiceInnovation variables have an effect of 18.4% on customer satisfaction, while Customer Service is4.9% and Customer Relationship Management (CRM) is 9.5%. Of the three, service innovation isthe dominant variable influencing consumer satisfactionKeywords: Service Innovation, Customer Service, Customer relationship Management,Customer Satisfaction